Prognostic significance of urothelial carcinoma with divergent differentiation in upper urinary tract after radical nephroureterectomy without metastatic diseases: A retrospective cohort study. Issue 21 (May 2017) - Qin, Chuan; Liang, En-Li; Du, Zhi-Yong; Qiu, Xiao-Yu; Tang, Gang; Chen, Fei-Ran; Zhang, Bo; Tian, Da-Wei; Hu, Hai-Long; Wu, Chang-Li
Abstract : Abstract: To evaluate the impact of urothelial carcinoma with divergent differentiation (UCDD) on the prognosis of patients for primary upper urinary tract urothelial carcinoma (UTUC) with pN0/x status treated with radical nephroureterectomy (RNU) and to evaluate the prognostic value of UCDD in different tumor locations (renal pelvis and ureter). Data from a total of 346 patients with UTUC who received RNU between January 2012 and March 2016 in the institution were retrospectively analyzed. Clinicopathological features and prognostic factors age, sex, complaint, height, weight, blood pressure, tumor grade, stage, smoking status, history of adjuvant chemotherapy, tumor location, history of bladder cancer, tumor necrosis, degree of hydronephrosis, tumor size, tumor focality, and preoperative anemia were compared between patients with pure UTUC and patients with UCDD. The endpoints were cancer-specific survival (CSS), overall survival (OS), and intraluminal recurrence-free survival (IRFS). Overall, divergent differentiation was present in 50 patients (14.5%). UCDD was related to different tumor location ( P = .01), smoking ( P = .04), higher body mass index ( P = .02), and advanced tumor grade ( P = .01). By Kaplan–Meier analysis, UCDD was found to be significantly correlated with worse IRFS, CSS, and OS (all P < .01). Multivariate analysis demonstrated that UCDD was an independent predictor of IRFS ( P < .01), CSS ( P = .01), and OS ( P = .01). However, 40 patients died for various reasons and the 5-year OS rates were 91.9% in UCDD− group and 68.0% in UCDD+ group, respectively. In patients with ureteral tumors, UCDD was the significant predictor for IRFS, CSS, and OS. However, the prognostic value of UCDD was not observed in pyelocaliceal tumors. The presence of divergent differentiation is associated with inferior survival. UCDD may identify patients at high risks for poor prognosis especially in patients with ureteral tumors. As a result, more attention and follow-up should be given to patients with ureteric urothelial carcinoma.